2015
DOI: 10.1111/radm.12153
|View full text |Cite
|
Sign up to set email alerts
|

The impact of organizational culture on a firm's capability to innovate the business model

Abstract: Recent literature on business model innovation tries to identify operational changes occurring within the business model components. We suggest that a significant part of the business model cannot be understood without an investigation of the underlying logic of the firm. Drawing on organizational culture literature, this study explores the idea that parts of the capabilities that enable business model innovation are determined by the firm's underlying cultural values. In this study, we utilize existing litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 81 publications
(235 reference statements)
3
101
0
1
Order By: Relevance
“…Empirical research has confirmed that two of these, strategic sensitivity and resource fluidity, indeed increase the propensity for business model innovation (Hock et al, 2015).…”
Section: Internal Drivers Of Business Model Innovationmentioning
confidence: 93%
See 2 more Smart Citations
“…Empirical research has confirmed that two of these, strategic sensitivity and resource fluidity, indeed increase the propensity for business model innovation (Hock et al, 2015).…”
Section: Internal Drivers Of Business Model Innovationmentioning
confidence: 93%
“…Overall, the literature indicates endogenous and exogenous sources of business model innovation. As for endogenous sources of business model innovation, they are related to the learning capabilities of the organisation (Sosna, Trevinyo-Rodríguez, & Velamuri, 2010), its strategic agility (Doz & Kosonen, 2010) and its organisational culture (Hock, Clauss, & Schulz, 2015). Sosna et al (2010) describe the case of Naturhouse to argue that business model innovation is an outcome of organisational learning processes, where trial and error are indispensable parts of business model innovation.…”
Section: Literature Review -Business Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…selling a product to providing solutions) (Laudien & Daxböck, 2016), which results in the alteration of routines, competences, technology and resources at the same time (Andries, Debackere, & van Looy, 2013). Radically novel business model may require internal transformational change in organizational culture (Hock, Clauss, & Schulz, 2015) to support new dominant logic and business model.…”
Section: Evolutionary Change For Moderately Novel Business Models In mentioning
confidence: 99%
“…Within business model innovation research, knowledge exchange with stakeholders is deemed crucial in relation to future business model development (Zott et al, ; Miller et al, ) However, organisational culture is said to underpin the capabilities needed for business model change (Matzler et al, ; Hock et al, ). Indeed, Wirtz et al (, p. 14) identifies the need to acknowledge ‘contextual differences between different business models as we are incapable to explain why certain models will function in particular environments and the others are not’ illustrating the influence organisational factors may have on business models development.…”
Section: Theoretical Development – Uttbm As An Activity Systemmentioning
confidence: 99%